F17 Juvenile onset huntington's disease: the health status and perspective of family carers. (September 2018) - Ho, Aileen; Quarrell, Oliver
Abstract : Introduction: Juvenile onset Huntington's disease (JOHD) is defined as onset ≤20 years. Although most patients are cared for within the family, the experiences of family-carers of JOHD is lacking. This study explores the perspective of JOHD family-carers together with their health status. Methods: Twenty six JOHD family-carers (with an average age 45 years) completed the EQ-5D questionnaire. They were also asked about their experience as carers and their responses were analysed qualitatively. Results: Family-carers reported positive elements, which were growth in the carer's character, strength of the JOHD patient's character, enriched family experiences, and supportive external relationships. Negative points reported were the personal and emotional toll on carers, toll on the family, and issues with external parties regarding JOHD. Carers' responses on what would be helpful centred on financial support, respite, and an increase in both the quantity and quality of services appropriate for JOHD. Family-carers' health status was lower than normal for their age group (EQ-5D visual analogue scale rating=73, EQ5-D index score=0.74). Pain/Discomfort was most affected in family-carers, followed by Mobility, with poorer scores for those caring for more severely affected JOHD patients. Conclusions: Family-carers face a high physical and emotional toll, especially when JOHD patients become severely affected. Greater understanding and acknowledgement of this is needed to address the health and quality of life of carers. [Research funded by the NHS National Institute for Health Research. Research for Patient Benefit stream. PB-PG-112–29056]